Reflections on the Murder of Trayvon Martin - Reston N. Bell; Tiffany J. Jones; Ricshawn Adkins Roane; Kidist M. Square; Rita Chi-Ying Chung (Journal for Social Action in Counseling and Psychology)
The tragic murder of 17-year-old Trayvon Martin in Sanford, Florida has quickly become the platform from which an entire movement has emerged. The first four authors, as members of the African American community, have elected to share their own personal experiences, reactions, and struggles with not only racial discrimination as it relates to the Trayvon Martin case, but racial discrimination in general for African Americans. The purpose of the article is to educate readers on the harsh realities of pervasive racism and to provide recommendations on ways it can be addressed. At the conclusion of this article, the authors have provided recommendations for training programs;educators and practitioners that will help them effectively work through instances of racial discrimination.